B2pin2-mediated copper-catalyzed oxidation of alkynes into 1, 2-diketones using molecular oxygen. Issue 12 (21st March 2019) - Zhai, Yadong; Su, Zhenni; Jiang, Hao; Rong, Jing; Qiu, Xianfan; Tao, Chuanzhou
Graphical abstract: Highlights: B2 pin2 as mediator, copper as catalyst. Molecular oxygen as the sole oxidant at room temperature. Versatile for various substituted alkynes, including diarylalkynes and arylalkylalkynes. Preliminary mechanism experiments indicated alkenyl borates are the key intermediates. Abstract: An intriguing aerobic oxidation of alkynes through copper catalysis is described, in which bis(pinacolato)diboron (B2 pin2 ) played a dominant intermediary role in the formation 1, 2-diketones. This novel protocol, which can be performed at room temperature, is versatile for various substituted alkynes, including diarylalkynes and arylalkylalkynes. The mechanism of this reaction was preliminarily investigated by control experiments.